2016
DOI: 10.1080/17686733.2016.1229246
|View full text |Cite
|
Sign up to set email alerts
|

Probability of detection analysis of round robin test results performed by flash thermography

Abstract: Within the scope of a standardisation research project, a flash thermography round robin test that evaluates reliability, comparability and efficiency of different testing situations was performed. Data recorded at metal test specimens with flat bottom holes (FBHs) were analysed by calculating the signal-to-noise ratio (SNR) of the defect signatures in the thermograms as well as in the phase images as a function of defect parameters. A new multi-parameter probability of detection (POD) model was developed, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The existing world experience of thermometry in medicine [1][2][3][4] at the first stage of the study, let us evaluate the temperature of the storage solution and transplants at different stages of the operation. It was found that the median temperature of the transplant is +5.4 °C in the storage solution of the generally recognized worldwide temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The existing world experience of thermometry in medicine [1][2][3][4] at the first stage of the study, let us evaluate the temperature of the storage solution and transplants at different stages of the operation. It was found that the median temperature of the transplant is +5.4 °C in the storage solution of the generally recognized worldwide temperature.…”
Section: Resultsmentioning
confidence: 99%
“…When considering the quality, capability and reliability of an SHM system, four fundamental influencing factors have been identified: algorithms, intrinsic factors, application factors and integration factors (see Table 1 ). Influencing factors have been widely studied in traditional NDE methods [ 33 , 34 , 35 , 36 ]. Although some of the factors apply to SHM methods as well, there are some differences to be considered.…”
Section: Need For Performance Assessment In Shmmentioning
confidence: 99%
“…The PoD is a quantitative measure of the capability of a non-destructive technique or methodology and allows the determination of the defect detection probability as a function of a parameter describing the defect geometry (ASME 3023-15) [2]- [3], [19]- [21]. This methodology should produce output that can be summarized within a representative quantitative signal, 'â', or a binary response, hit/miss.…”
Section: Probability Of Detection (Pod)mentioning
confidence: 99%
“…Up to now, there have been several studies concerning the determination of the PoD of standard and more conventional non-destructive methods like ultrasonics, eddy current, and radiography [22]- [23]. Some works also regard the application of active thermography with this purpose, in particular, lock-in and pulsed techniques, but considering in most cases FBHs defects [2]- [3]. In order to determine the PoD curve, a relationship between the variable that describes the defect and the one that characterizes the signal contrast is necessary [2]- [3], [19]- [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation